2022
DOI: 10.1002/jcp.30932
|View full text |Cite
|
Sign up to set email alerts
|

miRNA in Parkinson's disease: From pathogenesis to theranostic approaches

Abstract: Parkinson's disease (PD) is an age associated neurological disorder which is specified by cardinal motor symptoms such as tremor, stiffness, bradykinesia, postural instability, and non‐motor symptoms. Dopaminergic neurons degradation in substantia nigra region and aggregation of αSyn are the classic signs of molecular defects noticed in PD pathogenesis. The discovery of microRNAs (miRNA) predicted to have a pivotal part in various processes regarding regularizing the cellular functions. Studies on dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 227 publications
0
4
0
Order By: Relevance
“…There are many different studies to identify miRNA and disease relationships [27][28][29]. miR678 analysed in this study is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different studies to identify miRNA and disease relationships [27][28][29]. miR678 analysed in this study is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al (203) showed that AKT-mediated FoxO1 inactivation increases pathogenic mutant Huntington (mHtt) protein aggregates, yet another study showed that increasing FoxO1-dependent expression of autophagy, mitochondrial, and antioxidants genes improves HD symptoms including increased neuronal survival and enhanced motor control (204). Most studies of PD demonstrate that increased FoxO1 contributes to its pathology via increased inflammation and apoptosis (205,206). Evidence also suggests that FoxO1 mediates the depressive symptoms of PD (207).…”
Section: Foxo1 and T2dbrainmentioning
confidence: 99%
“…The presence of genetic material, such as miRNAs, is one of the largest common contents of exosomes [ 74 ]. Disorders like PD exhibit considerable disruption in gene expression, especially at the miRNA level [ 182 , 183 ]. Exosomes derived from MSCs can transfer miRNAs to neuronal cells.…”
Section: Msc-evs In Parkinson’s Diseasesmentioning
confidence: 99%